Teacher strategies for teaching slow learners in low-grade primary schools - Asri, Ovi Shinta; Nuroh, Ermawati Zulikhatin (Journal Of Teaching And Learning In Elementary Education, 2023)
Every child has the right to a proper education, including slow learners. Slow learners are students who experience delays in learning. The condition of students who experience learning delays causes low student achievement and difficulty understanding the material. Learning strategies are needed to help slow learners catch up. The research aims to describe the teacher's strategy for teaching slow-learning students with low grades. This type of research is qualitative research with a case study method. The research was conducted at SD Negeri Jemirahan with the participants being two grade 1 teachers. In this study, data collection techniques used observation, interviews, and documentation. The data were then analyzed using the Miles and Huberman model by reducing data, presenting data, and drawing conclusions. The results showed that teachers applied various strategies for slow-learning students in the form of material reduction, question modification, additional study hours, and seating rotation to student motivation. The results showed that the role of teachers with the application of appropriate learning strategies for slow learners had a significant impact, namely students' willingness to learn increased slowly.